Sintesis 4-Hidroksisinamamida dari Asam 4-Hidroksinanamat melalui Reaksi Esterifikasi dan Amonolisis - Firdaus Firdaus; Nunuk Hariani Soekamto; Abdul Karim (Hasanuddin University, 2009)
The 4-hydroxycinnamamide is a compound that has been isolated from the root bark of Kleinhovia hospita Linn. The compound show high toxicity to Artemia salina Leach (IC 180,53 µg) so it can be expected has cytostatic activity against P388 leukemic cells. However, the concentration of the compound in the root bark of K. hospita Linn is very low (about 1.6 ppm), and commercially the compound is not ready and has never been synthesized. Therefore, it is important to find out a synthesis method to used in prepare the compound for further examination, in particular its cytostatic activity. By this research, the 4-hydroxycinnamamide compound has been prepared from 4- hydroxycinnamic acid via esterification reaction with excess ethanol and sulphate acid catalyst followed ammonolysis reaction with concentrated ammonia. The esterification stage gave ethyl 4-hidroxycinnamate as white crystall with melting point 133-134oC and 34.9% yield, and the ammonolysis stage gave 4-hydroxycinnamamide as white crystall with merting point 140oC and 46.1% yield. Identification of the reaction product was carried out by FTIR and NMR spectroscopy methods.Keywords: 4-hydroxycinnamamide, 4-hydroxycinnamic acid, esterification, ammonolysis